The epidemiology and clinical spectrum of infections of the central nervous system in adults in north India. (January 2021) - Kumar, Devender; Pannu, Ashok Kumar; Dhibar, Deba Prasad; Singh, Rajveer; Kumari, Savita
Infections of the central nervous system (CNS) are a leading cause of mortality in low- and middle-income countries. We studied the spectrum, aetiology and outcome of CNS infections in 401 consecutive patients aged ≥12 years admitted at the medical emergency centre of PGIMER, Chandigarh, India. An aetiological diagnosis was made in 365 (91.0%) patients, with 149 (40.8%) microbiologically confirmed cases. CNS tuberculosis was the most prevalent cause (51.5%), followed by viral meningoencephalitis (13.9%), community-acquired bacterial meningitis (9.7%), cryptococcal meningitis (6.2%), scrub typhus meningoencephalitis (1.7%), neurocysticercosis (1.7%) and fungal brain abscess (1.7%). Human immunodeficiency virus (11.0%) and diabetes mellitus (6.2%) remained the usual predisposing conditions. We found a mortality rate of 27.9%, highest in cases without an aetiology (64.5%). Tuberculosis remained the most common cause; however, an increasing number of scrub typhus, dengue, fungal infections and non-classical bacterial pathogens may indicate a change in the epidemiology of community-acquired CNS infections in India.